2009
DOI: 10.1590/s1980-57642009dn30100007
|View full text |Cite
|
Sign up to set email alerts
|

Lack of executive function deficits among adult ADHD individuals from a Brazilian clinical sample

Abstract: Executive function deficits have been previously documented in individuals with Attention Deficit Hyperactivity Disorder (ADHD).ObjectiveThe current study aimed to compare measures of executive functions among a clinical sample of adults with ADHD and normal control subjects, matched for age, gender and education.MethodsTwenty-three self-referred adults diagnosed with ADHD according to DSM-IV criteria, and twenty-five control subjects were assessed using a neuropsychological battery which included the Wisconsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Similarly, ADHD patients in the present study who showed within-normal performance on every variable of the standard neuropsychological battery (Hi-ADHD) showed significant differences from controls on the experimental task aimed at evaluating real-life executive functioning. This is an important issue because other recent studies (Saboya, Coutinho, Segenreich, Ayrão, & Mattos, 2009) also failed to show executive deficits in a group of adult ADHD denoting low sensitivity of the standard executive tests to discriminate between controls and ADHD patients.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, ADHD patients in the present study who showed within-normal performance on every variable of the standard neuropsychological battery (Hi-ADHD) showed significant differences from controls on the experimental task aimed at evaluating real-life executive functioning. This is an important issue because other recent studies (Saboya, Coutinho, Segenreich, Ayrão, & Mattos, 2009) also failed to show executive deficits in a group of adult ADHD denoting low sensitivity of the standard executive tests to discriminate between controls and ADHD patients.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, they preferred novel options on the presentation of stimuli, heightening salience in their decision-making processes, and this salience explained 41% of the variance(Sethi et al 2018).Either way, FE ratings contribute significantly to the variance in ADHD symptoms and severity(Kamradt et al 2014), especially, ratings of inattentive symptoms provided by late-onset ADHD patients(Lin and Gua 2020).According to functional measures, EF deficits underlie the adaptive impairment associated with ADHD, but EF do not predict impairment independently of ADHD(Stavro et al 2007). When EF are assessed by ratings of daily life activities, they make some contribution to occupational impairments(Barkley and Murphy 2010) and deficits in daily life activities are shown(Barkley and Murphy 2011).Finally, some studies have found evidence of lowered performance in the general EF scope(Muller et al 2007;Salomone et al 2020), whilst other have found no differences in the typically deteriorated EF (In deBraek and Dijkstra 2011; Petersson et al 2018;Saboya et al 2009; Semrud-Clickemand and Harder 2010;Studerus et al 2018), although in some cases and in other cognitive domains they do find deficits(Torres et al 2017). No robust evidence of academic impairment is shown in ADHD group(Gropper and Tannock 2009).Regarding neuropsychological domains, between 73 and 82% adults with ADHD refer a large dysfunction in all domains of EF from a small to large size effect, with the exception of fluency tests(Fuermaier et al 2015).Separately, bilingualism has not been an advantage to compensate deficiencies in EF measures, contrary to IQ, which improves performance in EF tasks(Milioni et al 2017).…”
mentioning
confidence: 99%
“…Besides, compared with the control group, the prison inmates with ADHD showed poorer results on several measures of EFs and during controlling for IQ (Ginsberg, Hirvikoski, & Lindefors, ). However, some investigations have indicated that the executive dysfunctions are not consistently found in those with ADHD (Engelhardt, Nigg, Carr, & Ferreira, ; Epstein, Johnson, Varia, & Conners, ; King, Colla, Brass, Heuser, & von Cramon, ; Saboya, Coutinho, Segenreich, Ayrão, & Mattos, ); they have also revealed that cognitive deficits, especially problems with inhibitory processes, do not stretch far into adulthood. Moreover, many psychiatric disorders that are associated with ADHD are also related to executive dysfunctions (Pennington & Ozonoff, ; Seidman, Biederman, Faraone, Weber, & Ouellette, ); and this makes it difficult to determine whether the dysfunctions are attributable to ADHD, the presence of comorbid disorders or both.…”
mentioning
confidence: 99%